Method for manufacturing anode and method for manufacturing all-solid-state battery

JP7631912B2Active Publication Date: 2025-02-19TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021037201
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-02-19
Estimated Expiration
2041-03-09

AI Technical Summary

Benefits of technology

【0021】 本開示においては、コート層の発熱量低減機能の低下を抑制した負極を得ることができるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631912000002
    Figure 0007631912000002
  • Figure 0007631912000003
    Figure 0007631912000003
  • Figure 0007631912000004
    Figure 0007631912000004
Patent Text Reader

Abstract

To provide a manufacturing method of a negative electrode capable of suppressing degradation of heat generation reduction function of a coat layer.SOLUTION: A manufacturing method of negative electrode used in an all-solid battery includes: a coat layer forming step of forming a coat layer by coating a first slurry over a negative electrode current collector; and a negative electrode active material layer forming step of forming a negative electrode active material layer by coating a second slurry over the coat layer. The above problem is solved by providing the manufacturing method of negative electrode in such manner that: in the coat layer forming step and the negative electrode active material layer forming step, the coat layer and the negative electrode active material layer are formed so that, defining that (i) the edge angle of the coat layer in the coating width direction as θ1 and (ii) the edge angle of the negative electrode active material layer as θ2, θ2 / θ1>1 is satisfied; and defining that (ii) the width of coating droop of the coat layer in the coating width direction as W1 and the drop width of the negative electrode active material layer as W2, W2 / W1≤0.97 is satisfied.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a negative electrode. [Background technology]

[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.

[0003] Si-based active materials are known as negative electrode active materials with good capacity characteristics. Patent Document 1 discloses a negative electrode for a sulfide all-solid-state battery that contains at least one material selected from the group consisting of Si and a Si alloy as the negative electrode active material.

[0004] In addition, although not a technology related to all-solid-state batteries, Patent Document 2 discloses a negative electrode for a nonaqueous electrolyte secondary battery, which has a current collector, a first layer containing lithium titanate, and a second layer containing a carbon material, in which the ratio T1 / T2 of the thickness T1 of the first layer to the thickness T2 of the second layer is 0.15 or more and 0.55 or less.

[0005] Patent Document 3 discloses an all-solid-state battery containing a sulfide solid electrolyte and a halide solid electrolyte as the solid electrolyte. Patent Document 4 discloses a method for producing a battery electrode, which includes a coating step of coating a surface of a current collector with an electrode active material slurry containing an electrode active material and an electrolyte to form a coating film. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-142431 A [Patent Document 2] JP 2014-199714 A [Patent Document 3] International Publication No. 2019-135323 [Patent Document 4] JP 2020-087863 A Summary of the Invention [Problem to be solved by the invention]

[0007] For example, in order to reduce the amount of heat generated during a short circuit, it is effective to provide a coating layer (described later) between the negative electrode current collector and the negative electrode active material layer. On the other hand, for example, if an end of the negative electrode active material layer is electrically connected to the negative electrode current collector without the coating layer, that portion becomes an electronic conduction path, and the function of the coating layer to reduce the amount of heat generated is reduced.

[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a method for producing a negative electrode, which can obtain a negative electrode in which a decrease in the heat generation reducing function of the coating layer is suppressed. [Means for solving the problem]

[0009] In order to solve the above problems, the present disclosure provides a method for producing a negative electrode used in an all-solid-state battery, the method comprising: a coating layer forming step of coating a first slurry containing an oxide active material as a first active material onto a negative electrode current collector to form a coating layer; and a negative electrode active material layer forming step of coating a second slurry containing a second active material onto the coating layer to form a negative electrode active material layer, wherein in the coating layer forming step and the negative electrode active material layer forming step, the coating layer and the negative electrode active material layer are formed so as to satisfy: (i) when an end angle of the coating layer in the coating width direction is θ1 and an end angle of the negative electrode active material layer is θ2, θ2 / θ1>1; and (ii) when a coating sagging width of the coating layer in the coating width direction is W1 and a coating sagging width of the negative electrode active material layer is W2, W2 / W1≦0.97.

[0010] According to the present disclosure, by forming the coating layer and the negative electrode active material layer so as to satisfy (i) and (ii), a negative electrode in which the deterioration of the heat generation reducing function of the coating layer is suppressed can be obtained.

[0011] In the above disclosure, W2 / W1 may be 0.85≦W2 / W1.

[0012] In the above disclosure, the method for producing the negative electrode may include a pressing step of pressing the coating layer and the negative electrode active material layer in a thickness direction.

[0013] In the above disclosure, the method for producing the negative electrode may include a negative electrode tab forming step of forming a negative electrode tab including an end portion of the coating layer and an end portion of the negative electrode active material layer.

[0014] In the above disclosure, the first active material may be at least one of lithium titanate and niobium titanium based oxide.

[0015] In the above disclosure, the coating layer may contain at least one of a conductive material, a solid electrolyte, and a binder.

[0016] In the above disclosure, the ratio of the thickness of the coating layer to the thickness of the negative electrode active material layer may be 3% or more and 13% or less.

[0017] In the above disclosure, the second active material may have an overall expansion rate upon charging of 14% or more.

[0018] In the above disclosure, the second active material may be a Si-based active material.

[0019] The present disclosure also provides a method for producing an all-solid-state battery, the method including a negative electrode production step of producing a negative electrode by the above-described negative electrode production method.

[0020] According to the present disclosure, by producing a negative electrode by the above-described production method, it is possible to obtain an all-solid-state battery having a negative electrode in which the deterioration of the heat generation reducing function of the coating layer is suppressed. Effect of the Invention

[0021] The present disclosure provides an effect of obtaining a negative electrode in which the deterioration of the heat generation reducing function of the coating layer is suppressed. [Brief description of the drawings]

[0022] [Figure 1] 1A to 1C are schematic cross-sectional views illustrating a method for producing a negative electrode in the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating a negative electrode according to the present disclosure. [Diagram 3] FIG. 2 is a schematic plan view illustrating a negative electrode tab forming step in the present disclosure. [Figure 4] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 5] FIG. 2 is a schematic plan view illustrating a negative electrode prepared in an example. [Figure 6] FIG. 2 is a schematic plan view illustrating an evaluation sample prepared in the examples. [Figure 7] 1 shows the results of resistance measurement for evaluation samples prepared in Examples 1 to 4 and Comparative Examples 1 to 7. [Figure 8] 1 shows the results of resistance measurement for evaluation samples prepared in Examples 1 to 4 and Comparative Examples 1 to 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, the method for producing a negative electrode and the method for producing an all-solid-state battery in the present disclosure will be described in detail with reference to the drawings. Each of the figures shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in each of the figures, hatching showing the cross section of a member is appropriately omitted. In addition, in this specification, when expressing an aspect in which another member is arranged relative to a certain member, simply writing "above" or "below" includes both a case in which another member is arranged directly above or below a certain member so as to be in contact with the certain member, and a case in which another member is arranged above or below a certain member via another member.

[0024] A. Manufacturing method of negative electrode Fig. 1 is a schematic cross-sectional view illustrating a method for producing a negative electrode according to the present disclosure. In Fig. 1, first, a negative electrode current collector 1 is prepared (Fig. 1(a)). Next, a first slurry containing an oxide active material as a first active material is applied onto the negative electrode current collector 1 to form a coating layer 2 (Fig. 1(b)). Next, a second slurry containing a second active material is applied onto the coating layer 2 to form a negative electrode active material layer 3 (Fig. 1(c)). In this way, a negative electrode AN is obtained.

[0025] In the present disclosure, the coating layer and the negative electrode active material layer are formed so as to satisfy predetermined conditions. W In FIG. 2(a), the coating width of the coating layer is W1, and the coating width of the negative electrode active material layer 3 is W2. The coating width is an excess width (per one end) relative to the coating width W. For example, in FIG. 2(a), W The total width of the coating layer 2 at T In this case, usually, W T =W+2W1. In other words, the coating sagging width (W1, W2) is the width of the area that flows outward from the coating edge α. Also, as shown in Figure 2(b), WIn the figure, the end angle of the coating layer 2 is θ1, and the end angle of the negative electrode active material layer 3 is θ2. The end angle refers to the rising angle from the bottom surface at the end. In the present disclosure, the coating layer and the negative electrode active material layer are formed so as to satisfy (i) θ2 / θ1>1 and (ii) W2 / W1≦0.97. In the examples described later, W2 / W1 is approximately 1, and in Figs. 2(a) and (b), the dimensions are deformed for ease of understanding. As shown in Fig. 2(a), the end 3t of the negative electrode active material layer 3 is preferably located inside the end 2t of the coating layer 2. Furthermore, the end 3t of the negative electrode active material layer 3 is preferably located inside the abrupt decrease portion (the portion where the thickness decreases in the outward direction due to surface tension) including the end 2t of the coating layer 2. In addition, in the coating layer 2 shown in Figure 2(a), the region flowing outward from the coated end α has a sudden decrease portion and a gradual decrease portion (a portion where the rate of decrease in thickness in the outward direction is smaller than that of the sudden decrease portion), but the region flowing outward from the coated end α may have only a sudden decrease portion and not a gradual decrease portion.

[0026] According to the present disclosure, by forming the coating layer and the negative electrode active material layer so as to satisfy (i) and (ii), a negative electrode in which the deterioration of the heat generation reducing function of the coating layer is suppressed can be obtained. Here, as described above, in order to reduce the amount of heat generated, for example, during a short circuit, it is effective to provide a coating layer containing an oxide active material between the negative electrode current collector and the negative electrode active material layer. When Li is inserted into the oxide active material, electronic conductivity is exhibited, and when the inserted Li is desorbed, insulation is exhibited. Therefore, an increase in internal resistance can be suppressed by forming an electronic conduction path using the electronic conductivity of the oxide active material. On the other hand, for example, when a short circuit occurs, Li is desorbed from the oxide active material, and the amount of heat generated can be reduced by blocking the electronic conduction path using its insulation (shutdown function).

[0027] In this way, by providing a coating layer containing an oxide active material between the negative electrode current collector and the negative electrode active material layer, the amount of heat generated, for example, during a short circuit can be reduced. On the other hand, for example, if the end of the negative electrode active material layer is electrically connected to the negative electrode current collector without the coating layer, that part becomes an electronic conduction path, and the heat generation reduction function of the coating layer is reduced. In the present disclosure, by forming the coating layer and the negative electrode active material layer so as to satisfy (i) and (ii), it is possible to prevent the end of the negative electrode active material layer from being electrically connected to the negative electrode current collector without the coating layer, and to obtain a negative electrode in which the reduction in the heat generation function of the coating layer is suppressed.

[0028] 1. Coating layer formation process The coating layer forming step in the present disclosure is a step of applying a first slurry containing an oxide active material, which is a first active material, onto a negative electrode current collector to form a coating layer.

[0029] The method of applying the first slurry is not particularly limited, but is preferably a method that can apply the slurry in a predetermined width. In that case, a striped coating layer is obtained. A specific example of the method of applying the first slurry is a doctor blade method using an applicator. After the application of the first slurry, drying may be performed to remove the dispersion medium.

[0030] The first slurry contains an oxide active material as a first active material. The oxide active material usually has electronic conductivity when Li is inserted, and has insulating properties when the inserted Li is removed. The electronic conductivity (25° C.) of the oxide active material in the Li-inserted state is, for example, 8.0×10 -1 On the other hand, the electronic conductivity (25° C.) of the oxide active material in a state in which the inserted Li is released is, for example, 2.1×10 -6 S / cm or less.

[0031] The oxide active material contains at least a metal element and an oxygen element. The oxide active material preferably has at least one of a layered structure and a spinel structure. An example of the oxide active material is lithium titanate. Lithium titanate is a compound containing Li, Ti, and O, and is, for example, Li4Ti5O 12 , Li4TiO4, Li2TiO3, Li2Ti3O7. Other examples of oxide active materials include niobium titanium oxides. Niobium titanium oxides are compounds containing Ti, Nb, and O, such as TiNb2O7, Ti2Nb 10 O 29 The first slurry may contain only one type of oxide active material, or may contain two or more types of oxide active material. In addition, the oxide active material preferably has a Li insertion / extraction potential higher than that of the second active material.

[0032] The shape of the oxide active material may be, for example, particulate. The average particle diameter (D 50 ) is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle diameter (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. 50 ) can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM). The ratio of the oxide active material in the solid content of the first slurry is, for example, 50% by weight or more, or may be 70% by weight or more, or may be 90% by weight or more.

[0033] The first slurry usually contains a dispersion medium, the type of which is not particularly limited, but examples thereof include ketones such as diisobutyl ketone, alkanes such as heptane, and esters such as butyl butyrate.

[0034] The first slurry may or may not contain a conductive material. By adding a small amount of conductive material, the shutdown function works quickly and the amount of heat generated can be further reduced. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF).

[0035] The proportion of the conductive material in the solid content of the first slurry is, for example, 1% by weight or less, may be 0.5% by weight or less, or may be 0.3% by weight or less. The proportion of the conductive material may be 0% by weight or more than 0% by weight, and in the latter case, is, for example, 0.05% by weight or more.

[0036] The first slurry may or may not contain a solid electrolyte. By adding a solid electrolyte, a good ion conduction path is formed in the coating layer, the shutdown function works quickly, and the amount of heat generated can be further reduced. On the other hand, by not adding a solid electrolyte, an increase in internal resistance can be suppressed. Examples of solid electrolytes include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes.

[0037] Examples of the sulfide solid electrolyte include solid electrolytes containing Li, X (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen. Examples of the halogen include F, Cl, Br, and I. The sulfide solid electrolyte may be glass (amorphous), glass ceramic, or crystalline. Examples of the sulfide solid electrolyte include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2.

[0038] The proportion of the solid electrolyte in the solid content of the first slurry is, for example, 5% by volume or more, and may be 10% by volume or more, whereas the proportion of the solid electrolyte in the solid content of the first slurry is, for example, 30% by volume or less.

[0039] The first slurry preferably contains a binder. Addition of the binder improves the adhesiveness of the coating layer, and improves the adhesion between the negative electrode active material layer and the negative electrode current collector. Examples of the binder include fluoride-based binders, polyimide-based binders, and rubber-based binders. The content of the binder in the solid content of the first slurry is, for example, 1% by weight or more and 10% by weight or less.

[0040] The negative electrode current collector is a member that collects the current from the negative electrode active material layer. Examples of the negative electrode current collector include metal current collectors. Examples of the metal current collector include current collectors having metals such as Cu and Ni. The metal current collector may be a simple substance of the above metal, or an alloy of the above metal. Examples of the shape of the negative electrode current collector include a foil shape. The surface roughness (Rz) of the negative electrode current collector is, for example, 2 μm or more, may be 4 μm or more, or may be 6 μm or more. On the other hand, the surface roughness (Rz) of the negative electrode current collector is, for example, 9 μm or less.

[0041] 2. Negative electrode active material layer formation process The negative electrode active material layer forming step in the present disclosure is a step of applying a second slurry containing a second active material onto the coating layer to form a negative electrode active material layer. The negative electrode active material layer is preferably formed so as not to protrude from the coating layer in a plan view.

[0042] The method of applying the second slurry is not particularly limited, but is preferably a method that can apply the slurry with a predetermined width. In that case, a striped negative electrode active material layer is obtained. A specific example of the method of applying the second slurry is a doctor blade method using an applicator. After applying the second slurry, drying may be performed to remove the dispersion medium.

[0043] The coating width of the second slurry is W S The coating width of the first slurry is W F Let us assume that S / W F For example, W may be 1 or less than 1. S / W F is, for example, 0.8 or more, and may be 0.9 or more. The coating width of the slurry can be appropriately adjusted according to the shape of the target all-solid-state battery. The difference between the coating end when forming the negative electrode active material layer and the coating end when forming the coat layer is not particularly limited, but may be, for example, 1 cm or less, and may be 0.5 cm or less.

[0044] In the present disclosure, the coating layer and the negative electrode active material layer are formed so as to satisfy the following (i) and (ii). (i) When the end angle of the coating layer in the coating width direction is θ1 and the end angle of the negative electrode active material layer is θ2, θ2 / θ1>1. (ii) When the coating sagging width of the coating layer in the coating width direction is W1 and the coating sagging width of the negative electrode active material layer is W2, W2 / W1≦0.97

[0045] In (i), θ2 / θ1 is usually greater than 1, and may be 1.1 or greater, or may be 1.5 or greater. Meanwhile, θ2 / θ1 is, for example, 10 or less, or may be 5 or less. Each of θ1 and θ2 is, for example, 10° or more, or may be 20° or more, or may be 30° or more. Meanwhile, each of θ1 and θ2 is, for example, 70° or less, or may be 65° or less.

[0046] In (ii), W2 / W1 is usually 0.97 or less, may be 0.96 or less, or may be 0.95 or less. If W2 / W1 is too large, the heat generation reducing function of the coating layer may not be sufficiently suppressed. W2 / W1 is, for example, 0.80 or more, and may be 0.85 or more. If W2 / W1 is too small, the volumetric energy density of the all-solid-state battery may be small.

[0047] The coating layer and the negative electrode active material layer have two ends in the coating width direction. One of the ends may satisfy (i) and (ii), or both ends may satisfy (i) and (ii), with the latter being preferred.

[0048] The second slurry contains at least a second active material. The second active material is not particularly limited and may be a general negative electrode active material, but it is preferable that the second active material has a total expansion rate due to charging of 14% or more. This is because an active material having a large total expansion rate due to charging tends to have high capacity characteristics. In addition, when the capacity characteristics are high, the amount of heat generated during short circuit, for example, tends to be large. In the present disclosure, however, by providing the above-mentioned coating layer, it is possible to suppress an increase in the amount of heat generated while maintaining high capacity characteristics.

[0049] Here, graphite, which is known as a common negative electrode active material, has a total expansion rate due to charging of 13.2% (Simon Schweidler et al., “Volume Changes of Graphite Anodes Revisited: A Combined Operando X-ray Diffraction and In Situ Pressure Analysis Study”, J. Phys. Chem. C 2018, 122, 16, 8829-8835). That is, a second active material having a total expansion rate due to charging of 14% or more is an active material having a total volume expansion rate due to charging greater than that of graphite. The total volume expansion rate due to charging can be determined by space-group-independent evaluation as described in Simon Schweidler et al. The second active material may have a total expansion rate due to charging of 100% or more, or 200% or more.

[0050] An example of the second active material is, for example, a Si-based active material. The Si-based active material is an active material containing Si element. Examples of the Si-based active material include simple Si, Si alloys, and Si oxides. The Si alloy preferably contains Si element as a main component. Another example of the second active material is, for example, a Sn-based active material. The Sn-based active material is an active material containing Sn element. Examples of the Sn-based active material include simple Sn, Sn alloys, and Sn oxides. The Sn alloy preferably contains Sn element as a main component.

[0051] The shape of the second active material may be, for example, particulate. 50 ) is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less.

[0052] The ratio of the second active material in the solid content of the second slurry is, for example, 20% by weight or more, and may be 40% by weight or more. It may also be 60% by weight or more. On the other hand, the ratio of the second active material is, for example, 80% by weight or less. In addition, the second slurry usually contains a dispersion medium, and may contain at least one of a conductive material, a solid electrolyte, and a binder. These materials are the same as those in the first slurry described above.

[0053] In the present disclosure, the thickness of the coating layer is T1, and the thickness of the negative electrode active material layer is T2. The ratio of T1 to T2 (T1 / T2) is, for example, 3% or more, and may be 5% or more. If T1 / T2 is too small, it is difficult to obtain the effect of reducing the amount of heat generated. On the other hand, the ratio of T1 to T2 (T1 / T2) is, for example, 20% or less, and may be 13% or less, or may be 10% or less. If T1 / T2 is too large, the internal resistance is likely to increase.

[0054] T1 may be, for example, 2 μm or more, 3 μm or more, or 4 μm or more. Meanwhile, T1 may be, for example, 15 μm or less, or 10 μm or less. Meanwhile, T2 may be, for example, 20 μm or more, or 40 μm or more. Meanwhile, T2 may be, for example, 200 μm or less, or 150 μm or less.

[0055] 3. Pressing process The method for producing the negative electrode in the present disclosure may include a pressing step of pressing the coating layer and the negative electrode active material layer in the thickness direction. Pressing improves the density of the layers. Even if the end of the negative electrode active material layer is stretched outward by pressing, the coating layer and the negative electrode active material layer are formed so as to satisfy the above-mentioned (i) and (ii), thereby suppressing the deterioration of the heat generation reducing function of the coating layer.

[0056] Examples of the pressing method in the pressing step include plate pressing and roll pressing. The pressing pressure is, for example, 200 MPa or more, may be 400 MPa or more, or may be 600 MPa or more. The pressing pressure is, for example, 1000 MPa or less.

[0057] 4. Negative electrode tab formation process The method for producing a negative electrode according to the present disclosure may include a negative electrode tab forming step of forming a negative electrode tab including an end of the coating layer and an end of the negative electrode active material layer. By forming the coating layer and the negative electrode active material layer so as to satisfy the above-mentioned (i) and (ii), it is possible to prevent the end of the negative electrode active material layer from being electrically connected to the negative electrode current collector in the negative electrode tab without passing through the coating layer.

[0058] Fig. 3 is a schematic plan view illustrating the negative electrode tab forming step in the present disclosure. As shown in Fig. 3(a), by cutting so as to leave the end 2t of the coating layer 2 and the end 3t of the negative electrode active material layer 3, as shown in Fig. 3(b), a negative electrode tab 1T having the end 2t of the coating layer 2 and the end 3t of the negative electrode active material layer 3 is obtained. Examples of the cutting method include laser cutting, die pressing, and slitting.

[0059] B. Manufacturing method of all-solid-state batteries The method for producing an all-solid-state battery in the present disclosure includes a negative electrode production step of producing a negative electrode by the above-described negative electrode production method.

[0060] According to the present disclosure, by producing a negative electrode by the above-described production method, it is possible to obtain an all-solid-state battery having a negative electrode in which the deterioration of the heat generation reducing function of the coating layer is suppressed.

[0061] 1.Negative electrode manufacturing process The process for producing the negative electrode in the present disclosure is similar to that described above in "A. Method for producing the negative electrode," and therefore will not be described here.

[0062] 2. Positive electrode preparation process The manufacturing method of the all-solid-state battery in the present disclosure may include a positive electrode preparation step of preparing a positive electrode having a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode may be prepared by oneself or purchased from another party. The method of preparing the positive electrode is not particularly limited, but for example, a method of applying a positive electrode slurry containing a positive electrode active material onto a positive electrode current collector to form a positive electrode active material layer may be mentioned.

[0063] Examples of the material of the positive electrode current collector include metal and carbon. The positive electrode slurry contains at least a positive electrode active material and a dispersion medium, and may further contain at least one of a conductive material, a solid electrolyte, and a binder. Examples of the positive electrode active material include an oxide active material. The conductive material, the solid electrolyte, and the binder are the same as those described in "A. Method for manufacturing a negative electrode" above. The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0064] 3.Solid electrolyte layer preparation process The manufacturing method of the all-solid-state battery in the present disclosure may include a solid electrolyte layer preparation step of preparing a solid electrolyte layer. The solid electrolyte layer may be prepared by oneself or purchased from another party. The method of preparing the solid electrolyte layer is not particularly limited, but may be, for example, a method of coating a slurry for the solid electrolyte layer containing a solid electrolyte on a metal foil. The slurry for the solid electrolyte layer contains at least a solid electrolyte and a dispersion medium, and may further contain a binder. The solid electrolyte and the binder are the same as those described in "A. Manufacturing method of the negative electrode" above. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.

[0065] 4.Lamination process The method for producing an all-solid-state battery according to the present disclosure may include a lamination step of laminating a positive electrode, a solid electrolyte layer, and a negative electrode in the thickness direction in this order. Specifically, the layers are laminated such that the solid electrolyte layer is disposed between the positive electrode active material layer of the positive electrode and the negative electrode active material layer of the negative electrode.

[0066] 5.All-solid-state battery 4 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in FIG. 4 has a positive electrode CA having a positive electrode active material layer 5 and a positive electrode current collector 4, a negative electrode AN having a negative electrode active material layer 3, a coating layer 2 and a negative electrode current collector 1, and a solid electrolyte layer 6 disposed between the positive electrode active material layer 5 and the negative electrode active material layer 3.

[0067] The all-solid-state battery in the present disclosure is typically an all-solid-state lithium-ion secondary battery. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid automobiles, electric automobiles, gasoline automobiles, and diesel automobiles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid automobiles or electric automobiles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving bodies other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.

[0068] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0069] [Example 1] (Preparation of negative electrode current collector having coating layer) LTO particles (Li4Ti5O 12 LTO particles (average particle size 0.7 μm) and a binder (SBR) were prepared. These were weighed out so that the weight ratio of LTO particles:binder was 95:5, and mixed with a dispersion medium (diisobutyl ketone). The mixture obtained was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a slurry for the coating layer. The obtained slurry for the coating layer was applied onto a negative electrode current collector (Ni foil) by a blade coating method using an applicator, and dried under conditions of 100°C for 30 minutes. The coating width of the applicator was 90 mm. As a result, a negative electrode current collector 1 having a coating layer 2 (thickness 5 μm) was obtained, as shown in FIG. 5(a).

[0070] (Preparation of negative electrode) Si particles (average particle size 2 μm), sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li2S-0.25P2S5), average particle size 0.5 μm), conductive material (VGCF) and binder (SBR) were prepared. These were weighed out so that the weight ratio of Si particles: sulfide solid electrolyte: conductive material: binder was 47.0: 44.6: 7.0: 1.4, and mixed with a dispersion medium (diisobutyl ketone). The mixture obtained was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a negative electrode slurry. The obtained negative electrode slurry was applied onto the above-mentioned coating layer and dried under conditions of 100 ° C. for 30 minutes. The coating width of the applicator was 90 mm. As a result, a negative electrode having a negative electrode active material layer 3 (thickness 50 μm), a coating layer 2 and a negative electrode current collector 1 was obtained, as shown in FIG. 5 (b). The edge angle θ1 of the coating layer and the edge angle θ2 of the negative electrode active material layer, as well as the coating sagging width W1 of the coating layer and the coating sagging width W2 of the negative electrode active material layer, of the obtained negative electrode were measured using a laser microscope. The results are shown in Table 1.

[0071] (Preparation of evaluation samples) The obtained negative electrode was cut to a coating length L of 90 mm, as shown in Fig. 5(b). Then, as shown in Fig. 6, the two cut negative electrodes were arranged so that the negative electrode active material layers 3 faced each other, and pressed at 4 tons to obtain an evaluation sample.

[0072] [Examples 2 to 4, Comparative Examples 1 to 7] vinegar A negative electrode and an evaluation sample were obtained in the same manner as in Example 1, except that the solid content of the slurry was adjusted so that the end angles θ1, θ2 and coating drip widths W1, W2 shown in Table 1 were obtained.

[0073] [evaluation] The insulating properties of the evaluation samples prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were evaluated. Specifically, the resistance was measured using a circuit tester. Since the coating layer containing LTO that has not been charged is insulating, the insulating properties of the evaluation sample can be evaluated by measuring the resistance of the evaluation sample. The evaluation results are shown in Table 1, and in Figs. 7 and 8.

[0074] [Table 1]

[0075] As shown in Table 1 and FIG. 7, in Examples 1 to 4 and Comparative Examples 5 to 7, θ2 / θ1>1 was satisfied, and in that case, resistance on the order of MΩ was obtained. That is, it was confirmed that insulation was maintained between the two negative electrode current collectors. This is because the coating layer is insulating in an uncharged state. On the other hand, in Comparative Examples 1 to 4, the negative electrode active material layer protruded from the coating layer, so insulation was not maintained. Although the area of ​​the protruding portion was small, it is presumed that if, for example, a metal foreign object gets into the end portion, the heat generation reducing function of the coating layer will be significantly reduced.

[0076] In addition, as shown in Table 1 and FIG. 8, it was confirmed that in Examples 1 to 4, W2 / W1≦0.97 was satisfied, and the resistance was significantly higher than that in Comparative Examples 5 to 7. On the other hand, in Comparative Examples 5 to 7, it is presumed that the negative electrode active material layer slightly protruded from the coating layer during pressing, and the heat generation reducing function of the coating layer was slightly reduced. In this way, it was confirmed that the use of a negative electrode that satisfies θ2 / θ1>1 and W2 / W1≦0.97 can suppress the reduction in the heat generation reducing function of the coating layer. [Explanation of symbols]

[0077] 1...Negative electrode current collector 2…Coat layer 3...Negative electrode active material layer 4...Positive electrode current collector 5...Cathode active material layer 6...Solid electrolyte layer 10…All-solid-state battery

Claims

1. A method for producing a negative electrode for use in an all-solid-state battery, comprising the steps of: a coating layer forming step of applying a first slurry containing an oxide active material as a first active material onto a negative electrode current collector by a doctor blade method using an applicator to form a coating layer; a negative electrode active material layer forming step of applying a second slurry containing a second active material onto the coating layer by a doctor blade method using an applicator to form a negative electrode active material layer; having In the coating layer forming step and the negative electrode active material layer forming step, (i) The end angle of the coating layer in the coating width direction is θ 1 and the end angle of the negative electrode active material layer is θ 2 In this case, θ 2 / θ 1 > 1, and (ii) The coating sagging width of the coating layer in the coating width direction is W 1 The coating width of the negative electrode active material layer is W 2 In this case, W 2 / W 1 ≦0.97; The coating layer and the negative electrode active material layer are formed so as to satisfy When the coating width of the second slurry is W S and the coating width of the first slurry is W F , W S / W F is 1; the first active material is at least one of lithium titanate and niobium titanium oxide; The method for producing a negative electrode, wherein the coating layer does not contain a conductive material.

2. The W 2 / W 1 However, 0.85≦W 2 / W 1 The method for producing a negative electrode according to claim 1 ,

3. The method for producing a negative electrode according to claim 1 , further comprising a pressing step of pressing the coating layer and the negative electrode active material layer in a thickness direction.

4. The method for producing a negative electrode according to claim 1 , further comprising a negative electrode tab forming step of forming a negative electrode tab including an end portion of the coating layer and an end portion of the negative electrode active material layer.

5. The method for producing a negative electrode according to claim 1 , wherein the coating layer contains at least one of a solid electrolyte and a binder.

6. The method for producing a negative electrode according to claim 1 , wherein a ratio of a thickness of the coating layer to a thickness of the negative electrode active material layer is 3% or more and 13% or less.

7. The method for producing a negative electrode according to claim 1 , wherein the second active material has an overall expansion rate upon charging of 14% or more.

8. The method for producing a negative electrode according to claim 1 , wherein the second active material is a Si-based active material.

9. A method for producing an all-solid-state battery, comprising: a negative electrode production step of producing a negative electrode by the method for producing a negative electrode according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery and battery pack

    JP2010097720A

  • Secondary battery

    JP2011119216A

  • Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2014199714A

  • Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery including the same

    JP2016181331A

  • Negative electrode for sulfide all-solid battery, and sulfide all-solid battery and manufacturing method of the same

    JP2018142431A